Overview of prevention and treatment approaches: a summary from the European association for research on obesity in childhood “Prevention of Obesity” symposium - Moliterno, Paula; Widhalm, Kurt (Frontiers in Pediatrics, 2025)
With childhood obesity being one of the most common pediatric chronic diseases, years of extensive prevention experiences still show shortcomings. To gather a discussion over first-hand obesity prevention interventions, the European Association for Research on Obesity in Childhood and the Austrian Academic Institute for Nutritional Medicine organized an international symposium on “Prevention of Obesity” in October 2023 (Vienna, Austria). . This report aimed to summarize what researchers from Austria, Denmark, France, Germany, Italy, Portugal, Sweden, and Norway presented and discussed regarding different childhood obesity prevention (and treatment) models implemented in their countries. Using the Ecological Systems Theory framework, we mapped strategies across individual, interpersonal, organizational, community, and policy levels. Family-based interventions were considered best practices; education and counseling on parenting in the context of pediatric obesity is key, as well as using incentives, reminders, and feedback support. Financial support through sufficient personnel and materials budgets, interventions implementation, ongoing result analysis, and program sustainability was considered crucial for long-term success in preventing obesity. While most strategies focused on individual, interpersonal, and organizational levels, fewer directly addressed the community or policy levels, highlighting opportunities for more integrated, system-wide approaches.